Post-Devonian movement on the Fredericton Fault and tectonic activity in the New Brunswick Platform, central New Brunswick, Canada - Park, Adrian F.; Hinds, Steven J. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2019)
The Norumbega Fault system is traced from southern New England to Prince Edward Island, and its major strike-slip history is pre-Carboniferous. Carboniferous and later movements are less well constrained. Along the Fredericton Fault in western New Brunswick, offsets affect outcrops of Carboniferous strata in several ways. Revision of Carboniferous stratigraphy in this area using new miospore data and mapping of new exposures augmented by LiDAR imagery permits refinement of some of the post-Devonian movement history. The oldest post-Silurian unit recognized, the Longs Creek Formation, is fault-dissected and tightly folded, with faults and folds overlapped by the unconformity at the base of the upper Visean Shin Formation. The age of the Longs Creek Formation is uncertain and may be late Devonian to early Visean. Faults affecting the Shin Formation and Royal Road basalts are truncated by the unconformity at the base of the Bolsovian Minto Formation. Beneath this unconformity the presence of fault-bounded panels of vertical Langsettian strata (Boss Point and Deerwood formations) along the Fredericton Fault demonstrate late Visean to Serpukhovian, and post-Langsettian, pre-Bolsovian (Duckmantian) movements. At least three phases of movement can be seen affecting the Minto Formation. All the movement phases along the Fredericton Fault appear to be right-lateral strike-slip, except for one phase of post-Bolsovian left-lateral displacement.